Follow your “gut”—calling for colonoscopy in patients with upper gastrointestinal adenomas: a systematic review and meta-analysis - Hanyuan Xu; Kai Song; Yuelun Zhang; Chengzhen Lyu; Kun He; Wangyang Chen; Wei Chen; Dong Wu (Therapeutic Advances in Gastroenterology, 2025)
Background: Early detection and removal of adenomas through colonoscopy significantly reduces colorectal cancer (CRC) incidence and mortality. However, there is a lack of summarized evidence evaluating the necessity of colonoscopy in patients with upper gastrointestinal (UGI) adenomas. Objectives: We aimed to assess the risk of colorectal neoplasms in individuals with UGI adenomas to provide evidence on whether patients with UGI adenomas should undergo colonoscopy examination. Design: Systematic review and meta-analysis. Data sources and methods: A search of PubMed and Embase was performed up to November 30, 2024. The studies comparing the risk of colorectal neoplasms in patients with and without UGI adenomas were included. Pooled odds ratios (ORs) of colorectal adenomas were estimated using random-effects models. Trial sequential analysis (TSA) was performed to control for random errors. Results: A total of 15 studies with 210,508 participants were included. Our analysis revealed a significant association between UGI adenomas and an increased risk of colorectal adenomas (pooled OR 2.36, 95% confidence interval (CI), 1.82–3.06). TSA confirmed the reliability of these findings. In addition, the presence of duodenal adenomas was linked to an increased risk of advanced colorectal adenomas (pooled OR 2.95, 95% CI, 1.80–4.84) and CRC (pooled OR 2.15, 95% CI, 1.51–3.06). Sensitivity analyses supported the robustness of these associations. Subgroup analysis suggested that patients with either gastric or duodenal adenomas had a higher risk of colorectal adenomas. Conclusion: This is the first meta-analysis suggesting that patients with UGI adenomas are at increased risk of colorectal adenomas and CRC. These findings highlight the need for colonoscopy in this patient population and supplement colonoscopy screening guidelines. Trial registration : This meta-analysis protocol was registered on PROSPERO (CRD42024623610).